Into the Classroom / The Complete Guide for Student Teachers - Bousted Mary; Fletcher Kat (ATL - The Education Union)
Your School or College Placement, Joining the Teaching Profession, Arriving at School or College, Essential Information, Professional Expectations, Some Ideas to Heplp You During your First Few Weeks, Organisation, Rights and Responsibilies, Time Management, Problem Solving, Looking After Yourself, Sources of Support.